1992
DOI: 10.1080/15298669291359357
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Blood Formate Accumulation in Humans Following Exposure to Methanol Vapor at the Current Permissible Exposure Limit of 200 ppm

Abstract: Accumulation of formate, the putative toxic metabolite of methanol, in the blood and the relationship between pulmonary intake and blood methanol concentration were investigated in six human volunteers following a 6-hr exposure to 200 ppm methanol (the current Occupational Safety and Health Administration 8-hr time-weighted average permissible exposure limit). At the end of a 6-hr exposure to 200 ppm methanol at rest, the blood methanol concentration was increased from a mean of 1.8 micrograms/mL to 7.0 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…A number of experimental and ®eld studies have addressed the relationship between inhalation exposures to methanol and biological indicators, including methanol and formate in end-shift urine and methanol in blood (e.g., Leaf and Zatman 1952;Sedivec et al 1981;Kawai et al 1991Kawai et al , 1992Franzblau et al 1992bFranzblau et al , 1997Yasugi et al 1992) as well as breath monitoring (Lee et al 1992;Franzblau et al 1992aFranzblau et al , 1995. Methanol readily passes into and through the skin, and the role of the dermal exposure pathway has been demonstrated in several reports (Dutkiewicz et al 1980;Franzblau et al 1995;Batterman et al 1996a;Batterman and Franzblau 1997).…”
Section: Introductionmentioning
confidence: 97%
“…A number of experimental and ®eld studies have addressed the relationship between inhalation exposures to methanol and biological indicators, including methanol and formate in end-shift urine and methanol in blood (e.g., Leaf and Zatman 1952;Sedivec et al 1981;Kawai et al 1991Kawai et al , 1992Franzblau et al 1992bFranzblau et al , 1997Yasugi et al 1992) as well as breath monitoring (Lee et al 1992;Franzblau et al 1992aFranzblau et al , 1995. Methanol readily passes into and through the skin, and the role of the dermal exposure pathway has been demonstrated in several reports (Dutkiewicz et al 1980;Franzblau et al 1995;Batterman et al 1996a;Batterman and Franzblau 1997).…”
Section: Introductionmentioning
confidence: 97%
“…pectine, aspartame) and is formed additionally by the metabolism. In humans levels usually range below 1-2 lg/mL blood (Lee et al, 1992). • Acute toxicity…”
Section: Toxicological Profilementioning
confidence: 99%
“…Lee et al (67) demonstrated that after a 6-hr exposure to the current methanol threshold limit value (TLV) of 200 ppm, the formate does not accumulate in blood in human subjects at rest or during exercise. This result was confirmed by other authors (68,6p).…”
Section: Renal Tumorsmentioning
confidence: 99%